Evaluasi Pengelolaan Aset Tetap pada Kantor Kesyahbandaran dan Otoritas Pelabuhan (KSOP) Kelas I Dumai - Twenty Mariza Syafitri; Akhmad Hasid Siregar (Politeknik Raflesia Press, 2025)
Fixed asset administration is an important part of an organization's financial management. The Ministry of Transportation as the parent organization of the Dumai Harbormaster and Port Authority Office (KSOP) has issued regulation No. 70 of 2018 concerning procedures for administering state-owned goods within the Ministry of Transportation. This research aims to analyze the percentage level of conformity between the administration of fixed assets of the Dumai KSOP Office with Minister of Transportation Regulation No. 70 of 2018. The sample for this research is 75 item of fixed assets with a acquisition price of >50 million which are on the List of Goods until 2023. This research uses a study approach cases with purposive sampling research subjects. Data collection was carried out by interviews, observation and documentation. The research results show that the Dumai KSOP Office is in the appropriate category for implementing Minister of Transportation Regulation No. 70 of 2018 with a score of 73%. Evaluation of fixed asset administration procedures showed the following results: 72% for fixed asset bookkeeping activities, 67% for fixed asset inventory activities, 81% for fixed asset reporting activities, and 74% for completeness of filling in goods identity cards (KIB). These findings indicate that there are areas that require improvement, but overall, the Dumai KSOP Office has complied with the regulations set out in Minister of Transportation Regulation No. 70 of 2018.